WHAT RECENT STUDIES TALK ABOUT MASTER PLAN - Silva, William Ferreira da; Campos Lima, Fabiano (Geoambiente On-line, 2023)
Master Plan is an important tool for urban policies and most municipalities have this document to guide their planning. It can explain and shows the path through which cities have passed, and above all indicate the path to follow. Aimed to assess data concerning the MP, we searched on Periódicos CAPES scientific database, papers published in the last five years containing the “city master plan” or “plano diretor” in title or keywords. Applying the inclusion/exclusion criteria we found 42 papers, 32 (76.19%) published in Portuguese, 9 (21.43%) in English and 1 (2.38 %) in Spanish. Brazilian cities were mentioned in 26 (60.47%). Many aspects of the MP were addressed such as urban management, concept and design, climate changes and popular participation. The importance of popular participation to construct the MP was explored in 8 (19.05%) studies, mainly relating the theme to Brazilian cities. Environmental implications were also another recurring theme explored. All papers presented general aspects of the MP. The MP is a comprehensive issue that allows discussion from different themes and its application certainly wide and must be explored in its entirety.